The Impact of Payment Systems and Peer-to-Peer Lending on the Performance of SMEs in Indonesia - Desiyanti, Rika; Azilah Husin, Nor; Azlina Md Kassim, Aza; Elvira, Rini (KnE Social Sciences, 2022)
SME performance has contributed to the establishment and sustainability of the nation’s economy. This paper aimed to analyze the effect of payment systems and peer-to-peer lending on the performance of SMEs. A questionnaire was distributed to SMEs in Sumatra, Indonesia, using an area random sampling technique, and 387 respondents were obtained. The study found that payment systems and peer-to-peer lending do affect the performance of SMEs. Keywords: payment system, peer-to-peer lending, SMEs’ performance